Neuropathology of microglia and oligodendrocytes - Butt, Arthur M. (Henry Stewart Talks, 2011)
Microglia, Oligodendrocytes, Degeneration, SC in PNS injury, CNS degeneration, Mechanisms of axon growth inhibition by myelin proteins, Oligodendrocyte precursor cells (NG2-glia), Demyelination, Multiple sclerosis